Global healthcare use by immigrants in Spain according to morbidity burden, area of origin, and length of stay - Luis A. Gimeno-Feliu; Amaia Calderón-Larrañaga; Esperanza Diaz; Beatriz Poblador-Plou; Rosa Macipe-Costa; Alexandra Prados-Torres (BMC, 2016)
Abstract Background The healthcare of immigrants is an important aspect of equity of care provision. Understanding how immigrants use the healthcare services based on their needs is crucial to establish effective health policy. Methods This retrospective, observational study included the total population of Aragon, Spain (1,251,540 individuals, of whom 11.9 % were immigrants). Patient-level data on the use of primary, specialised, hospital, and emergency care as well as prescription drug use in 2011 were extracted from the EpiChron Cohort and compared between immigrants and nationals. Multivariable standard or zero-inflated negative binomial regression models were generated, adjusting for age, sex, length of stay, and morbidity burden. Results The annual visit rates of immigrants were lower than those of nationals for primary care (3.3 vs 6.4), specialised care (1.3 vs 2.7), planned hospital admissions/100 individuals (1.6 vs 3.8), unplanned hospital admissions/100 individuals (2.7 vs 4.7), and emergency room visits/10 individuals (2.3 vs 2.8). Annual prescription drug costs were also lower for immigrants (€47 vs €318). These differences were only partially attenuated after adjusting for age, sex and morbidity burden. Conclusion In a universal coverage health system offering broad legal access to immigrants, the global use of healthcare services was lower for immigrants than for nationals. These differences may be explained in part by the healthy migration effect, but also reveal possible inequalities in healthcare provision that warrant further investigation.